Correction: Klentrou et al. Circulating Levels of Bone Markers after Short-Term Intense Training with Increased Dairy Consumption in Adolescent Female Athletes. Children 2021, 8, 961 - Panagiota Klentrou; Katherine McKee; Brandon J. McKinlay; Nigel Kurgan; Brian D. Roy; Bareket Falk (MDPI AG, 2023)
There was an error in the original publication [...]